Transformasi Bioekonomi Kehutanan Berbasis Nilai-Nilai Aswaja: Model Konseptual Penguatan Ekonomi Sektor Riil di Indonesia - Mahfudz Mahfudz; Khulfi Muhammad Khalwani; Muhamad Alkaf (BRILIANT: Jurnal Riset dan Konseptual, 2026)
The growing complexity of non-military threats requires Indonesia to strengthen national resilience through approaches that extend beyond conventional defense institutions. In this context, forest bioeconomy, gender equality, and community-based social values have strategic relevance for enhancing non-military defense. This study aims to develop a conceptual framework integrating gender equality in forest bioeconomy based on the values of Ahlussunnah wal Jama'ah (Aswaja) promoted by Nahdlatul Ulama as a strategy to strengthen Indonesia's non-military defense. The research employed a qualitative approach using the Integrative Literature Review (ILR) method by synthesizing scientific publications, institutional theories, social capital literature, and relevant national policy documents. The findings indicate that Aswaja values function as informal institutions that provide social legitimacy for gender equality, while gender-inclusive forest bioeconomy enhances governance quality, women's participation, social capital, collective action, and community resilience. These interrelated processes contribute to strengthening national capacity in addressing non-military threats through improved food, energy, water, environmental, economic, and social resilience. The main contribution of this study is the development of an interdisciplinary conceptual framework connecting institutional theory, gender studies, forest bioeconomy, social capital, and non-military defense within the Indonesian context. This framework provides a theoretical foundation for integrating forestry development, gender mainstreaming, and national defense policies toward Indonesia Emas 2045.